2019
DOI: 10.4274/balkanmedj.galenos.2019.2018.12.11
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Bone Density Reduction in Rats Caused by Unilateral Nasal Obstruction

Abstract: Background:Oral breathing can cause morphological changes in the oral and maxillofacial regions.Aims:To investigate whether oral breathing affected structural changes in bone tissues.Study Design:Animal experimentation.Methods:A total of 48 8-day-old male Sprague−Dawley rats were divided into two groups: a breathing group and a sham (control) group. All Sprague−Dawley rats were killed at 7 weeks after unilateral nostril obstruction modeling. Then, structural changes in bone tissues were detected by micro-compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…It has been reported that nasal obstruction negatively affects alveolar bone. 12 , 13 However, considering that previous studies were conducted using neonatal rats, our study provides meaningful data on the effect of nasal obstruction in adolescents.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that nasal obstruction negatively affects alveolar bone. 12 , 13 However, considering that previous studies were conducted using neonatal rats, our study provides meaningful data on the effect of nasal obstruction in adolescents.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the current basic research suggests that the OPG/RANKL ratio may be more meaningful than the OPG levels alone during osteoclast formation. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that hypoxia can lead to oxidative stress and apoptosis in periodontal tissue. After modeling UNO in rats, rats presented with oral respiratory symptoms [24][25][26]. Oral respiration is one of the main clinical manifestations in patients with OSAHS [1].…”
Section: Discussionmentioning
confidence: 99%
“…Model. A UNO rat model was established by cauterizing the external nostril [24][25][26]. Briefly, 8-day-old male Wistar rats (n = 30) were randomly divided into two groups: SHAM and UNO.…”
Section: Animals and Unilateral Nasal Obstruction (Uno)mentioning
confidence: 99%
See 1 more Smart Citation